Aortic root and left atrial wall motion. An echocardiographic study. Issue 10 (October 1977) - Akgün, G; Layton, C
Abstract : The echocardiographically recorded movement of the aortic root was studied by analysing the relation between posterior aortic wall motion and other intracardiac events. The systolic anterior movement of the aortic root continued beyond aortic valve closure and in cases with mitral regurgitation began significantly earlier than in normal subjects. The diastolic rapid posterior movement began after mitral valve opening but did not occur in patients with mitral stenosis. The total amplitude of aortic root motion was increased in patients with mitral regurgitation, diminished in cases of mitral stenosis, and was normal with aortic regurgitation. In patients with atrioventricular block an abrupt posterior movement followed the P wave of the electrocardiogram irrespective of its timing in diastole. These observations correlate with the expected changes in left atrial volume during the cardiac cycle both in the normal subjects and patients with heart disease. The results support the hypothesis that phasic changes in left atrial dimension are largely responsible for the echocardiographically observed movement of the aortic root and indicate a potential role for echocardiography in the analysis of left atrial events.